Depressive symptoms and suicidal ideation among Vietnamese students aged 13–17: Results from a cross-sectional study throughout four geographical regions of Vietnam - Quynh Anh Tran (Health Psychology Open, 2020)
We conducted a cross-sectional study in four provinces located in four different geographical areas in Vietnam to examine the prevalence and associated factors of depression and suicide ideation among school students aged 13–17. A sample of 6407 students from secondary school and high school participated in our survey to complete self-reported questionnaires. Depressive symptoms were measured by the Center for Epidemiologic Studies Depression scale (CES-D). Suicidal ideation and associated factors were measured by the Global School Student Health Survey (GSHS) questionnaire. We found that 31.7% of students had depressive symptoms, and 11% reported suicidal ideation during the last year. Female students and older students were more at risk of experiencing depressive symptoms and suicidal ideation than male students and younger students. Bullying, violence, smoking, and alcohol consumption appear as risk factors, while a good relationship with parents/guardians may protect school students from having depressive symptoms and suicidal ideation.